2018
DOI: 10.3390/catal8120631
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photocatalytic Activity of Titania by Co-Doping with Mo and W

Abstract: Various W and Mo co-doped titanium dioxide (TiO2) materials were obtained through the EISA (Evaporation-Induced Self-Assembly) method and then tested as photocatalysts in the degradation of 4-chlorophenol. The synthesized materials were characterized by thermogravimetric analysis (TGA), Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), Raman spectroscopy (RS), N2 physisorption, UV-vis diffuse reflectance spectroscopy (DRS), X-ray photoelectron spectroscopy (XPS), and transmission electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…Such a presence of oxygen vacancies proves the existence of sub-stoichiometric metal oxides in our catalysts. It is worth commenting that Zr cation in ZrO 2 is energetically very difficult to reduce [31,32]. The charge state of zirconium is expected to be either 0 as in the case of metal, or +4 as in ZrO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Such a presence of oxygen vacancies proves the existence of sub-stoichiometric metal oxides in our catalysts. It is worth commenting that Zr cation in ZrO 2 is energetically very difficult to reduce [31,32]. The charge state of zirconium is expected to be either 0 as in the case of metal, or +4 as in ZrO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The significant Raman bands associated with rutile are noted around 439.26 cm −1 and 602.94 cm −1 , respectively. As compared to pure anatase, the E g peaks of Mo-TiO 2 are red shifted with an increase of line width [71]. The peak shift is explained by a number of competitive mechanisms, such as phonon confinement, lattice strain/ distortion and non-stoichiometric defects due to oxygen vacancies [72][73][74][75].…”
Section: Raman Spectramentioning
confidence: 95%
“…Apart from Ti 3+ ions, other transition metals, such as copper (Cu), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe) and nickel (Ni), are typically employed to enhance the visible-light photocatalytic activity of titania [88][89][90][91][92][93][94][95][109][110][111][112][113][114][115]. The redshift effectiveness takes the following order: V > Cr > Mn > Fe > Ni [86].…”
Section: Metal Dopingmentioning
confidence: 99%
“…This is typically termed the 'co-doping'. The enhancement in the photocatalytic activity of co-doped TiO 2 is attributed to the synergistic effect of the dopants in increasing visible light absorption, thus facilitating electron-hole generation and suppressing the recombination rate [90,[113][114][115]. Very recently, Aviles-Garcia et al synthesized W and Mo co-doped TiO 2 , and reported that the nanocomposite with the W:Mo = 1:1 ratio having a bandgap of 2.87 eV exhibits a synergistic effect between the dopants to generate more hydroxyl radicals for degrading 4-chlorophenol.…”
Section: Metal Dopingmentioning
confidence: 99%